Online Hostel Automation - K.V, Chandrashekar; C S, Kishor kumar; B, Monisha; A, Nikitha; Appaji, Impana (IJRDO -Journal of Computer Science Engineering, 2017)
The online hostel automation system is web based software. This document is intended to minimize human works and make hostel allocation is an easier job for students and hostel authorities by providing online application for hostel, automatically select the students from the waiting list and mess calculation, complaint registration, notice board etc. Students will get approval notification in their mails. Hostellers can view notice board, hostel fee and mess menu by logging into online system. It helps to notify parents regarding their wards and their presence in hostel and their curricular will be notified to their parents using this model just in one touch and it also makes online payment and over viewing of balance fee amount easier than before. The attendance of students or the hostellers will be recorded using bio-metric so that no duplications or complications will be created and it also makes easy to maintain and record about mess investments, expenditures and details about whole hostel and hence everything will be transparent to the founder or the owner.